The effects of transparency perceptions on trustworthiness perceptions and trust. Issue 1 (2nd January 2022) - Tomlinson, Edward C.; Schnackenberg, Andrew
ABSTRACT: Transparency is recognised as vital to ensuring employee trust in managers. However, prior measures of transparency have made it difficult to discern the precise influence of transparency on trust. We posit that separate dimensions of transparency perceptions (disclosure, clarity, and accuracy) uniquely influence perceptions of trustworthiness (ability, benevolence, and integrity). We also posit that trustworthiness, as the proximal predictor of trust, mediates the transparency-trust relationship. Using a recently published measure of transparency that captures its dimensions, we find support for our predictions that transparency differentially influences trust via trustworthiness across two samples with unique referents (direct manager and top-management-team). Our results show that employees place trust in different ways depending on how much information they perceive their managers to be sharing (i.e. disclosure), what they perceive their managers to be revealing (i.e. accuracy), and how they perceive their managers to be revealing it (i.e. clarity). Thus, managers who are seen as satisfying some dimensions of transparency but not others (e.g. disclosure and accuracy, but not clarity) might not foster needed trustworthiness perceptions for employees to justify placing trust in the manager, with practical implications for managers seeking to develop trust in situations that require them to demonstrate specific trustworthiness attributes.